The communication process in oncology: Reporting an experience - Moro Gutiérrez, Lourdes; Kern de Castro, Elisa; González Fernández-Conde, Marta (Psicooncología, 2014)
Telling someone that he/she suffers cancer is a deep shock for the individual and its family as well. The disease involves physical, psychological and social changes that both the patient and his/her social environment have to learn to cope with. Cancer is still readily associated with pain and death, so patients have to face a dramatic and distressing situation. For achieving an emotionally and physically smooth treatment of cancer it is necessary to develop a comprehensive and holistic approach split into three stages. First, information provided about diagnosis and care possibilities. Secondly, the communication process along the treatment period, which may be rather long. Third, and particularly prominent, the communication process during the last stage of the disease, whether it disappears or leads to death. This paper presents our experience on the overall information and communication process with cancer patients who undergo chemotherapy treatment. It is essential to deal with information and communication on a personalized basis for each individual, so our conclusions are focused on the basic topics which have to be addressed for each patient to receive the information the most suitable for his/her particular case.
Keywords: Cancer; information; communication.